Rockburst Occurrence Mechanism Based on the Self-Sustaining Time-Varying Structure of Surrounding Rock. (27th October 2020) - Fan, Baojie; Zhao, Fujun; Wang, Bin; Wu, Qiuhong; Zhang, Zongtang
Abstract : Rockburst is one of the major disasters that threaten the safety of personnel and equipment underground and affect the normal production of the system. At present, there are many kinds of research on rockburst occurrence mechanisms, but most of them are based on statics and do not consider the time-varying effect of surrounding rock state. Regarding the stress state and characteristics changing with time of the surrounding rock support structure and the internal parameters after the tunnel excavation is analyzed qualitatively in this paper, the concept of the "self-sustaining time-varying structure of the surrounding rock" is put forward. The "self-sustaining time-varying structure of the surrounding rock" is regarded as a nonperiodic time-varying system with a single degree of freedom, then its dynamic characteristics are analyzed by using the momentum theorem of the particle system. The results show that when the mass of the self-sustaining time-varying structure changes with time and d m / d t < 0, the rockburst may be induced by the free vibration with increasing amplitude. The faster the d m / d t changes, the more violent the rockburst is. This explains the rockburst occurrence mechanism from a new angle and explains the phenomenon that most rockburst occurs when σ θ was lower than σ c better.